2016
DOI: 10.1126/sciadv.1501292
|View full text |Cite
|
Sign up to set email alerts
|

Targeting NF-κB in glioblastoma: A therapeutic approach

Abstract: Inhibition of the transcription factor NF-κB or its target genes should be considered for the treatment of patients with glioblastoma multiforme.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
91
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 119 publications
(96 citation statements)
references
References 36 publications
5
91
0
Order By: Relevance
“…S8D,E). In conjunction with this result, a survivin promoter reporter construct (−1000 base pairs [bp] to +1) containing these NF-κB response elements showed that promoter activity was stimulated upon vIII-CM treatment and that its activity was efficiently inhibited by IκB superrepressor (IκB-SR) (Friedmann-Morvinski et al 2016) or deletions of the three NF-κB-binding sites (Fig. 4C).…”
Section: Nf-κb Regulates Survivin Expression In Gbmmentioning
confidence: 64%
See 1 more Smart Citation
“…S8D,E). In conjunction with this result, a survivin promoter reporter construct (−1000 base pairs [bp] to +1) containing these NF-κB response elements showed that promoter activity was stimulated upon vIII-CM treatment and that its activity was efficiently inhibited by IκB superrepressor (IκB-SR) (Friedmann-Morvinski et al 2016) or deletions of the three NF-κB-binding sites (Fig. 4C).…”
Section: Nf-κb Regulates Survivin Expression In Gbmmentioning
confidence: 64%
“…A variety of stimuli can activate NF-κB-mediated transcription, among which wtEGFR and EGFRvIII have been reported to activate NF-κB (Dan et al 2008;Tanaka et al 2011;Cahill et al 2016). In this regard, NF-κB has been shown to be a major molecular driver of chemotherapy and radiotherapy resistance in GBM (Tanaka et al 2011;Bhat et al 2013;Cahill et al 2016;Friedmann-Morvinski et al 2016). To inhibit survivin expression, we chose the epigenetic regulator JQ1, which targets the bromodomain-containing factor BRD4, known to maintain NF-κB in an active state and regulate the enhancer-mediated function of this transcription factor (Brown et al 2014;Zou et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, MWCNTs induced the expression of a panel of cell cycle control genes in WT lungs, but induction was significantly reduced in Timp1 KO lungs (Figure 5A and B); MWCNTs stimulated the proliferation of fibroblasts in WT lungs but not in Timp1 KO lungs (Figure 5C); and co-treatment of primary mouse lung fibroblasts with MWCNTs and TIMP1 neutralizing antibodies largely reduced the proliferation of fibroblasts induced by MWCNTs in vitro (Figure S12). Other studies have also suggested a role for TIMP1 in boosting cell proliferation in several in vitro and in vivo models (Bertaux et al, 1991; Chesler et al, 1995; Friedmann-Morvinski et al, 2016; Hayakawa et al, 1992; Xia et al, 2012). Therefore, our results describe a novel underlying mechanism for MWCNT-induced lung fibrosis through the TIMP1-dependent proliferation of fibroblasts.…”
Section: Discussionmentioning
confidence: 95%
“…For instance, MMPs have both inhibitory and stimulatory activities toward fibrosis in addition to ECM degradation (Giannandrea & Parks, 2014). On the other hand, the MMP-independent functions of TIMP1, such as promoting cell proliferation and survival, have received increasing attention, particularly for cancer cells (Friedmann-Morvinski et al, 2016; Xia et al, 2012). In this regard, our study provides the in vivo evidence to support the MMP-independent function of TIMP1 in promoting cell proliferation in induced organ fibrosis.…”
Section: Discussionmentioning
confidence: 99%
“…Others have identified alterations in the NF-κB pathway itself, with a subset of GBMs harboring monoallelic NFKBIA (gene name for IκBα) deletions and others expressing high levels of miR-30e* which targets IκBα [34, 35]. Consistent with the involvement of NF-κB signaling in GBM, recent work demonstrated that treatment with a NEMO-binding domain (NBD) peptide that blocks interactions between NEMO and IKKα/β slowed tumor growth in both a human glioma xenograft and a genetic mouse model of glioma [36]. …”
Section: Introductionmentioning
confidence: 99%